2000
DOI: 10.1007/s001340000635
|View full text |Cite
|
Sign up to set email alerts
|

Different dosages of dobutamine in septic shock patients: determining oxygen consumption with a metabolic monitor integrated in a ventilator

Abstract: With a metabolic monitor integrated in a ventilator it was possible to carry out continuous monitoring of calorimetric data under clinical conditions. In contrast to previous studies using indirect calorimetry, this study showed a moderate correlation between VO2 and DO2 in septic patients using either method. The clinical relevance of this finding requires further investigation. Different factors (e. g. injectant temperature, pulmonary VO2) produced substantial differences between VO2,IC and VO2,Fick as previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…In the second patient DO 2 increases by 300 ml min ±1 M ±2 with a 10 % slope, which suggests VO 2 /DO 2 independence. VO 2 was significantly increased in the patients investigated by Schaffartzik et al [5], from 173 to 188 ml min ±1 M ±2 , which could suggest VO 2 /DO 2 dependence. However, these patients had been in a stable hemodynamic condition for more than 6 h, so that VO 2 /DO 2 dependence was very unlikely.…”
Section: How To Interpret Changes In Vo2?mentioning
confidence: 83%
See 4 more Smart Citations
“…In the second patient DO 2 increases by 300 ml min ±1 M ±2 with a 10 % slope, which suggests VO 2 /DO 2 independence. VO 2 was significantly increased in the patients investigated by Schaffartzik et al [5], from 173 to 188 ml min ±1 M ±2 , which could suggest VO 2 /DO 2 dependence. However, these patients had been in a stable hemodynamic condition for more than 6 h, so that VO 2 /DO 2 dependence was very unlikely.…”
Section: How To Interpret Changes In Vo2?mentioning
confidence: 83%
“…Fourth, various studies have shown good agreement between calculation of VO 2 using the Fick principle and indirect calorimetry [14,15]. In this issue, Schaffartzik et al [5] report that agreement between the two methods of approx. 20 %.…”
Section: Mathematical Couplingmentioning
confidence: 95%
See 3 more Smart Citations